Biomas brasileiros: espaço ocupado como objeto de pesquisa em programas de pós-graduação científica - de Souza, Débora Velasque; Cunha, Fernando Icaro Jorge; Castro, Luis Roberval Bortoluzzi; Dinardi, Ailton Jesus (Góndola, enseñanza y aprendizaje de las ciencias, 2022)
Brazilian biomes have been suffering drastically from the environmental impacts caused mainly by agribusiness and other means of production that use natural resources. Even though it is a relevant subject, there are many records of failures within the teaching and learning process about Brazilian Biomes in Basic Education. Thus, the present study aimed to analyze, qualitatively and quantitatively, research on the topic of Brazilian Biomes, in graduate programs in Science Teaching and Science Education, in the last ten years, to understand whether this subject is also neglected as a research theme. For this, a systematic review was carried out to recognize the production of dissertations and theses on “Biomes” in the Graduate Programs of public universities located in the five regions of Brazil between 2011-2020. Results show the number of studies found is not enough to debate that problem, nor contribute to an efficient teaching and learning process. In the same way, researchers found the aim, for the most part, to investigate and not promote actions that can bring improvements to the educational context and thus favor environmental awareness.